A burden or a boost: The impact of early childhood English learning experience on lower elementary English and Chinese achievement. Issue 4 (21st April 2022) - Chen, Si; Zhao, Jing; de Ruiter, Laura; Zhou, Jing; Huang, Jinzhen
ABSTRACT: We examined the effect of learning English as a foreign language in early childhood on children's later English and Chinese achievement and attitude toward English learning in mainland China. A total of 892 children were divided into two groups according to whether they had any English learning experience before they entered elementary school. To reduce self-selection bias in children's early English learning experience, we employed propensity score matching (PSM) and coarsened exact matching (CEM) techniques and generated balanced samples based on children's demographic, parent-child interactional and socio-economic characteristics. We found that the experience of early childhood English learning alone positively contributed to later English language and Chinese language achievement and also to attitudes toward English learning. The findings provide important evidence that limited exposure to English before elementary school does not harm Chinese learning. They also have educational implications that encourage educators to continue helping students develop genuine interest in English learning and maintain their high level of motivation starting at a very young age.